Quality improvement: audio-visual tools are a valuable supplement when obtaining consent for lumbar punctures. Issue 3 (2016) - Berner, Alison May; Craven, A Claudia; Laskou, B Faidra; Baudracco, C Irene; Graham, D Neil; F, E Cath Mummery; Ingle, Gordon
No abstract available